2006
DOI: 10.1074/jbc.m604616200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Tissue Inhibitor of Metalloproteinases-1 Activation by Interleukin-1 in Primary Human Astrocytes

Abstract: Reactive astrogliosis is the gliotic response to brain injury with activated astrocytes and microglia being the major effector cells. These cells secrete inflammatory cytokines, proteinases, and proteinase inhibitors that influence extracellular matrix (ECM) remodeling. In astrocytes, the expression of tissue inhibitor of metalloproteinases-1 (TIMP-1) is up-regulated by interleukin-1 (IL-1), which is a major neuroinflammatory cytokine. We report that IL-1 activates TIMP-1 expression via both the IKK/NF-B and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…Using Western blotting, we also show TIMP-1, but not TIMP-2, induction in LPStreated astrocytes, in agreement with previous results in glial cultures (Liu et al, 2007;Liuzzi et al, 2004;Wilczynska et al, 2006). Also, a number of in vivo results, including from our laboratory, indicate that TIMP-1 is induced at high levels in reactive astrocytes (Jaworski, 2000;Rivera et al, 1997Rivera et al, , 2002Wilczynska et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using Western blotting, we also show TIMP-1, but not TIMP-2, induction in LPStreated astrocytes, in agreement with previous results in glial cultures (Liu et al, 2007;Liuzzi et al, 2004;Wilczynska et al, 2006). Also, a number of in vivo results, including from our laboratory, indicate that TIMP-1 is induced at high levels in reactive astrocytes (Jaworski, 2000;Rivera et al, 1997Rivera et al, , 2002Wilczynska et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The apparent discrepancy between these results and our data showing clear MMP-9 expression and LPS-driven upregulation in astrocytes may result from fundamental differences between primary cells and stem cells, which undergo in vivo and in vitro differentiation, respectively, and may be related to differential expression by primary and stem cells of CD14 or LPS-binding protein (LBP), both important for LPS-induced effects in cells (Guillemin et al, 1997;Kitchens, 2000). Using Western blotting, we also show TIMP-1, but not TIMP-2, induction in LPStreated astrocytes, in agreement with previous results in glial cultures (Liu et al, 2007;Liuzzi et al, 2004;Wilczynska et al, 2006). Also, a number of in vivo results, including from our laboratory, indicate that TIMP-1 is induced at high levels in reactive astrocytes (Jaworski, 2000;Rivera et al, 1997Rivera et al, , 2002Wilczynska et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…26 To determine whether aldosterone induces TIMP-1 expression via the effect of NF-κB or AP-1, we used NF-κB and AP-1 decoy oligodeoxynucleotides to block the downstream response. Human cardiac fibroblasts were pretreated with decoy oligodeoxynucleotides before 10 -6 M aldosterone treatment, and the results showed that the aldosterone-induced expressions of protein and TIMP-1 mRNA were both suppressed by NF-κB decoy oligodeoxynucleotide, but not by AP-1 decoy oligodeoxynucleotide ( Figure 3A-3B).…”
Section: Aldosterone Induced Timp-1 Expression Via Nf-κbmentioning
confidence: 99%
“…10 Next to the MMPs, plasmin is a broad-spectrum protease that also hydrolyzes many extracellular proteins, the most notable of which is fibrin. Plasmin is produced from an inactive precursor called plasminogen.…”
Section: Relationship Between Nf-jb and The Angiogenic Processmentioning
confidence: 99%